Malware distributed collection and pre-classification system using honeypot technology - Grégio, André R. A.; Oliveira, Isabela L. [UNESP]; Santos, Rafael D. C.; Cansian, Adriano M. [UNESP]; DeGeus, Paulo L. (My University, 2009)
Malware has become a major threat in the last years due to the ease of spread through the Internet. Malware detection has become difficult with the use of compression, polymorphic methods and techniques to detect and disable security software. Those and other obfuscation techniques pose a problem for detection and classification schemes that analyze malware behavior. In this paper we propose a distributed architecture to improve malware collection using different honeypot technologies to increase the variety of malware collected. We also present a daemon tool developed to grab malware distributed through spam and a pre-classification technique that uses antivirus technology to separate malware in generic classes. © 2009 SPIE.
Keywords: Honeyclients; Honeypots; Information systems security; Malicious software; Malware collection; Computer software; Information management; Information systems; Internet; Intrusion detection; Mining; Computer crime